(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
London stands as one of the preeminent global cities, serving as a cornerstone in the world’s financial network, a vibrant cultural capital, and a melting pot of diverse communities. This article explores London’s economic significance, its rich cultural landscape, and the urban challenges it faces. Through a comprehensive review of existing literature and a qualitative analysis of key urban metrics, this study aims to highlight London’s multifaceted identity and its pivotal role on the global stage